G14(P) A collaborative educative approach to invest in enablement of transition: closing the gap between children's and adult services. (27th April 2015) - Gelder, C; MacArthur, C; Phillips, A; Morgan, S; Campbell, F; Redfern, S; Smalley, A; Rudd, K; Evans, P
Abstract : Aims: An overview of the creation, delivery, evaluation and impact of a collaboratively designed health professional degree and master's module supporting establishment, augmentation and enhancement of transitional services across long term conditions, life threatening illnesses, learning disability and mental health provision. Methods: A collaborative engaged multi-disciplinary module team with a combined vision to develop practitioners' knowledge, skills and abilities concerning effective transition opportunities worked together. We designed an interactive blended-learning module supported by nationally recognised experts in the field, on-line resources and access to the RCPCH Adolescent health module. The module was delivered and evaluated exceptionally well. Students were assessed design and presentation of their proposals to change and develop their services to be more 'adolescent and transition friendly'. The written assessment was a report to be delivered within the students areas of practice to facilitate the changes intended to realise development of effective transition services accordingly. The module was delivered at level 6 and level 7 to support a multi-disciplinary team approach to embracing transition. Local Education Training Board (LETB) funding supported student attedance. Results: Students included Nurses, Doctors, Dietitians, Psychologists and Youth Workers evaluated the module excellently and highlighted opportunities realised within their own practices and specialisms. This demonstrated a change in thinking, renewed energy to face change and tackle potential challenges to providing effective transition. Synergistic opportunities were also realised by managers and commissioners attending the students' presentations and 'signing up' to supporting the fresh approaches and ideas within their services to enable effective transition to be appreciated. Key outcomes for students and practice: Developing a clearer vision through action planning, thus developing a wealth of knowledge and resources to stimulate change. Heightened motivation and confidence facilitated renewed energy to initiate practice communication with adult service colleagues. Students had 'a voice' rather than hierarchy intimidating their vision for their team. The action plans met patients' needs for improvement and development to close service gaps. Conclusion: Quality transition services can be realised rather than just 'talked about'. Practitioners are engaged in critical discussions to effect this transformation and are implementing service improvement. Crucially and incrementally managers and commissioners have pledged their support to escalate and influence essential changes in practice.